THERMAL ANALYSES OF COORDINATION-COMPOUNDS .2. THERMAL-DECOMPOSITION OF PALLADIUM COMPLEXES WITH TRIPHENYLPHOSPHINE, TRIPHENYLARSINE AND TRIPHENYLSTIBINE - Barbieri, R. S.; Belatto, C. R.; Massabni, A. C. (Wiley-Blackwell, 1995)
The compounds [PdCl(2)L(2)] and [PdL(4)] (L=PPh(3), AsPh(3), SbPh(3)) were studied by thermogravimetric and differential thermal analyses in air. The residues of thermal decomposition consist of metallic palladium, except in the case of the complexes containing SbPh(3), when the residues are palladium and antimony mixtures in appropriate proportions with respect to the stoichiometry of the related complexes.
Keywords: PALLADIUM COMPLEXES; THERMAL ANALYSIS